A new teacher's guide : surviving your first year - Singer, Harvey, 1940- (Lanham, Md. : Scarecrow Press, 2003)
Publisher's description: For many years, new teachers have complained that they were not well prepared for many of the daily realities of classroom teaching. Based on Singer's personal experience as a teacher, dean, counselor, and administrator, this book will provide specific tools and insights to help new teachers become successful in assisting students with a variety of issues including drug abuse, legal matters, and communication with parents. Intended for beginning teachers.
First thoughts -- The first day -- The technical side of learning -- The personal side of learning -- Communicating effectively -- Discipline -- Drug abuse -- Working with your colleagues -- A few words about administrators -- Playing by the rules -- It's all about students -- Finding a job -- Surviving your first year...and beyond -- The last Chapter.
"A ScarecrowEducation book."
Keywords: First year teachers; Teacher effectiveness